Liberation and Authority Plato's Gorgias, the First Book of the Republic, and Thucydides - Thorne, Nicholas (Lexington Books, 2021)
Liberation and Authority provides original, comparative readings of Plato's Gorgias, the first book of the Republic, and Thucydides' History, arguing that they share similarities not only in the oft-noted "natural justice" of Callicles, Thrasymachus, and the Melian Dialogue, but also in a development that runs through the whole of each.